Photovoltaic-pyroelectric effect coupled broadband photodetector in self-powered ZnO/ZnTe core/shell nanorod arrays. (August 2019) - You, Daotong; Xu, Chunxiang; Zhang, Wei; Zhao, Jie; Qin, Feifei; Shi, Zengliang
Abstract: Broadband photodetection is widely used in commercial and military fields. However, most semiconductor-based detectors face the constraint of light absorption, needing external bias, comparatively lower responsivity and slower response time that limit their practical applications. Herein, a self-powered core/shell photodetector was fabricated by sputtering a uniform p-type ZnTe layer on n-type ZnO nanorod array. By integrating pyroelectric and photovoltaic effects, the photodetector realizes broadband detection from 325 nm ultraviolet to 1064 nm near infrared under zero bias. The maximum responsivity and detectivity reach 196.24 mA/W and 3.47 × 10 12  cm Hz 1/2 /W for 325 nm laser illumination with power density 2.13 mW/cm 2, respectively, which are improved 10-fold relating to the device responded to photovoltaic effect only. While the rise and fall time are drastically reduced from 1.222 ms to 62 μs and 1.563 ms to 109 μs, respectively. In addition, the effects of light wavelength, power density and bias voltage on photocurrent response induced by photovoltaic-pyroelectric effect are systematically characterized and discussed. Our work not only provides a easy yet efficient procedure to construct broadband photodetector, but also broadens the application prospects of core/shell nanorod array based on photovoltaic-pyroelectric effect. Graphical abstract: A facile vapor phase transport and sputtering procedure was used to fabricate self-powered ZnO/ZnTe core/shell nanorods photodetector. Based on pyroelectric and photovoltaic effects, the photodetector exhibited broadband sensitivity from 325 nm ultraviolet to 1064 nm near-infrared light and fast response speed (62 μs).Image 1 Highlights: We develop a facile strategy to fabricate perfect n-ZnO/p-ZnTe core-shell nanorod arrays and construct a photodetector. By integrating pyroelectric and photovoltaic effects, this self-powered photodetector shows a broadband responsefrom UVto NIR. The maximum responsivity and detectivity reach 196.24 mA/W and 3.47 × 10 12  cm Hz 1/2 /W for 325 nm illumination, respectively. The rise and fall time are drastically reduced from 1.222 ms to 62 μs and 1.563 ms to 109 μs, respectively.